The environmental benefits of eucalyptus planting: literature review (Research, Society and Development, 2021)
In 2019, planted forests totaled 9.0 million hectares, an increase of 2.4% compared to 2018. Of this total, the majority (77%) is represented by eucalyptus, with about 6.97 million hectares, and 18% of pine, with 1.64 million hectares. Eucalyptus plantations are widely accepted in Brazil due to their rapid growth, high productivity, their multiple products (paper, cellulose, furniture, wood panels, floors, charcoal, civil construction) and is also related to the profitability generated by it. But, despite all these positive factors of its planting, there are still many myths related to the negative impacts generated by eucalyptus on the environment. In this context, the research aimed to highlight the positive environmental impacts of eucalyptus plantations, observing their influence on soil, water, protection of native forests, nutrient cycling and carbon fixation. For this, a narrative literature review was carried out and, as an inclusion criterion, scientific articles, journals, periodicals were considered, free of charge and in full, in Portuguese, Spanish and English. Comparing eucalyptus with other agricultural and forestry crops, it was found that its planting consumes less water and retains nutrients. There was a consensus in the literature about the beneficial impacts of planting eucalyptus on the soil, protecting against erosion by water, water, protection of native forests and retaining large amounts of CO2 from the atmosphere, improving air quality.